Ultrasound-Induced Escherichia coli O157:H7 Cell Death Exhibits Physical Disruption and Biochemical Apoptosis - Li, Jiao; Ma, Luyao; Liao, Xinyu; Liu, Donghong; Lu, Xiaonan; Chen, Shiguo; Ye, Xingqian; Ding, Tian (Frontiers in Microbiology, 2018)
Ultrasound has attracted great interest of both industry and scientific communities for its potential use as a physical processing and preservation tool. In this study, Escherichia coli O157:H7 was selected as the model microbe to investigate the ultrasound-induced cell death. Slight variations in membrane potential and ion exchanges across membrane induced by low-intensity ultrasound increased the membrane permeability of E. coli O157:H7, and this reversible sublethal effect can preserve the viability of E. coli O157:H7 and meanwhile be beneficial for bioprocessing application. In comparison, high-intensity ultrasound resulted in irreversible lethal effect on E. coli O157:H7, which can be applied in the field of microbial inactivation. In addition, both low- and high-intensity ultrasound induced either physical destruction or trigger genetically encoded apoptosis of E. coli O157:H7. Accumulation of reactive oxygen species and decrease of adenosine tri-phosphate might be related to the physiological and biochemical hallmarks of apoptosis, including exposed phosphatidylserine and activated caspases in E. coli O157:H7. The result provides novel insight into the mechanisms of non-thermal physical treatment on the inactivation of bacteria, and lays foundation for the further research on the cell signaling and metabolic pathway in apoptotic bacteria.